1973
DOI: 10.1128/aem.25.3.442-446.1973
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Growth of Pseudomonas fluorescens in Liquid Egg White

Abstract: Pseudomonas fluorescens grew rapidly in fresh egg albumen diluted with water. Growth of the bacteria in egg albumen was stimulated by the addition of carbohydrate and ovomucoid-rich egg exudate. Polyacrylamide-gel electrophoresis for residual egg albumen revealed extensive proteolysis of albumen inoculated with the organism. A fluorescent compound with absorption maximum at 408 nm was isolated from a defined salt medium inoculated with P. fluorescens. It shortened the lag phase and increased the final cell yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Our results of water, iron, egg yolk and glucose treatments given to EW corroborate results of other investigators (Ayers and Taylor, 1956;Garibaldi and Stokes, 1958;Brown et al, Nath and Baker, 1973). These authors have suggested a number of mechanisms like the lack of free water required for the dissolution of nutrients and the nonavailability of proper nutrients required for the growth of bacteria for explaining EW resistance to bacterial growth.…”
Section: Effect Of Additivessupporting
confidence: 90%
See 1 more Smart Citation
“…Our results of water, iron, egg yolk and glucose treatments given to EW corroborate results of other investigators (Ayers and Taylor, 1956;Garibaldi and Stokes, 1958;Brown et al, Nath and Baker, 1973). These authors have suggested a number of mechanisms like the lack of free water required for the dissolution of nutrients and the nonavailability of proper nutrients required for the growth of bacteria for explaining EW resistance to bacterial growth.…”
Section: Effect Of Additivessupporting
confidence: 90%
“…SEVERAL FACTORS such as the lack and nonavailability of proper nutrients, lysozyme which lyses the Gram-positive bacteria, ,avidin and ovotransferrin (sequestering agent) which deprive bacteria of biotin and iron respectively, and high pH have been held responsible for the resistance of egg white (EW) to bacterial growth (Ayers and Taylor, 1956;Board et al, 1968;Vadehra and Nath, 1973). These theories, however, neither explain the susceptibility of EW to proteolytic pseudomonads (Garibaldi and Stokes, 1958), nor the ability of aging (Brown et al, 1965) and water treatment (Nath and Baker, 1973) to render EW suitable to bacterial growth. Proteolysis, alkaline hydrolysis due to aging and precipitation of ovomucin due to water treatment all alter the physical structure of EW drastically.…”
Section: Introductionmentioning
confidence: 99%